Role of Sentiment Analysis in consumer research: A case study of Reliance Jio - Savitha Nair, Dr (Journal of Contemporary Research in Management (JCRM), 2017)
Sentiment analysis provides insights from social data beyond social KPIs. It is evolving as one of the useful research methods in marketing and involves the processing of natural language and text to understand electronic word-of-mouth (eWOM) that are expressions of consumers’ attitudes and feelings towards brands or topics in online conversations. Today, consumers converse online using several social media platforms such as Facebook, Twitter etc. People write, comment and express their emotions on almost everything including brands, movies and other social events and activities in these platforms. The social engagement that happens through these sites is available to the marketer in real time and they act as one of the important sources of marketing intelligence. Marketers and researchers have accepted the fact that social communities have a significant impact on consumer behavior. With a huge amount of user generated content available online at a comparatively cheaper rate, sentiment analysis can be used as an alternative research method to complement the traditional qualitative and quantitative consumer research. This study explores the scope of sentiment analysis based on literature review. Consumer sentiments on Reliance Jio during its pre and post launch phases are analyzed based upon user comments and insights are drawn. The study confirms the application of sentiment analysis in bringing out an integrated perspective in online consumer research.